Analysis of the Causes of High Internal Temperature in the TMC Type-54EWNA Control Air Compressor on MV Pan Africa - Nazha Madeza Bakri; Abdi Seno; Dirhamsyah; Antonius Edy Kristiyono; Teguh Pribadi (Journal of Engineering Science and Technology Management, 2026)
The control air compressor is one of the important auxiliary machines in the compressed air system on board a ship, which functions to supply air for both manual and automatic pneumatic control systems. One of the problems that frequently occurs in this equipment is an increase in internal temperature (high internal temperature) in the Control Air Compressor TMC Type 54-EWNA, which can reduce compressor performance and increase the risk of damage and operational disturbances. This study aims to analyze the causes of high internal temperature in the control air compressor and to determine appropriate corrective and preventive measures. The methods used in this study include direct observation, interviews, and documentation, as well as analysis using the Fishbone analysis method. The results of the analysis indicate that the main causes of increased internal temperature include suboptimal cooling system performance, deterioration of lubrication quality, inconsistent implementation of the Planned Maintenance System (PMS), as well as the influence of environmental conditions and materials experiencing corrosion. The root cause identified is a lack of supervision and irregularity in maintenance implementation. The recommended efforts to address these problems include optimizing the cooling system, using and replacing oil, filters, and coolers according to specifications, carrying out periodic maintenance in accordance with the PMS and manual book, and improving monitoring of compressor operating parameters. By implementing these measures, it is expected that the compressor’s internal temperature can be controlled, compression pressure remains optimal, and the reliability and safety of the ship’s compressed air system can be maintained.